Solving the Dynamic Plant Layout Problem using a new hybrid meta-heuristic algorithm. (2nd May 2007) - Rodriguez, Jose M.; MacPhee, F. Chris; Bonham, David J.; Bhavsar, Virendrakumar C.
The Quadratic Assignment Problem (QAP) can be used to formulate the Facility Layout Problem (FLP). The Dynamic Plant Layout Problem (DPLP) extends the FLP. Of the attempted 48 DPLP instances, 29 now have new best-known solution. With respect to the six department instances that all have a known optimal solution, optimal solutions were obtained for two, for which no heuristic had been found before, and previously found optimal solutions were matched for the remainder. With respect to the 15 and 30 department instances, none of which has a known optimal solution, only three current best-known solutions could not be obtained.